Isolation and Characterization of a Molybdenum Reducing Enzyme in Enterobacter cloacae Strain 48 - Abd. Shukor, Mohd. Yunus; Lee, C. H.; Omar, Ismail; Karim, M. I. A.; Syed, Mohd Arif; Shamaan, Nor Aripin (Universiti Putra Malaysia Press, 2003)
Molybdenum reducing enzyme was isolated from Enterobacter cloacae Strain 48 by ammonium sulphate fractionation, DE-cellulose ion-exchange chromatography and Sephacryl S-200 gel filtration. SDS-PAGE of the concentrated Sephacryl S-200 gel filtration eluates revealed the presence of 3 protein subunits of molecular weight 80, 90 and 100 kDa. The active concentrated fraction from the Sephacryl S-200 gel filtration step was then characterized for molybdenum reducing activity with 12-molybdophosphate (12-MoP) as a substrate. The optimum pH and temperature of the reaction was 5.0 and 28-33°C, respectively. ADH was a better reducing agent in the reaction than NADPH; the double reciprocal plot of activity against ADH and NADPH revealed apparent Km and V""", values of 1.65 mM, 6.28 nmole molybdenum blue produced/min/mg and 2.13 mM and 4.10 nmole molybdenum blue produced/min/mg, respectively. The double reciprocal plot of activity against 12-MoP and 20-molybdodiphosphate revealed apparent K m values of 0.3 mM and 0.4 mM, respectively. The apparent Vmax values are similar for both substrates at 6 nmole molybdenum blue produced/min. The assay method for molybdenum reducing activity using 12-MoP was found to be easier and more rapid than the present method of using molybdate as a substrate